Solid electrolyte, preparation method thereof and battery
By using polymers with supramolecular structure and specific repeat units in solid electrolytes and combining lithium salts, the problems of poor conductivity and mechanical strength of traditional solid electrolytes are solved, and efficient lithium ion transmission and battery safety are achieved.
Patent Information
- Application Number
- CN202411810120.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Traditional polymer solid electrolytes have problems with poor conductivity and mechanical strength, which limits their application in lithium batteries.
Using a solid electrolyte including specific polymers and lithium salts, the polymer is formed by supramolecular structure and non-covalent bonds (such as hydrogen bonds, π-π stacking), combining repeating units of ether oxygen bonds, six-membered rings and benzene rings to improve mechanical strength and conductivity.
It realizes the high conductivity and mechanical strength of solid electrolytes, and is suitable for all-solid lithium metal high-energy batteries, improving the cycling performance and safety of the batteries.
Smart Images

Figure CN119812452A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a solid electrolyte and a preparation method thereof, and a battery. Background Art
[0002] In order to alleviate the energy crisis and implement the "dual carbon" goals, the green energy sector has flourished. Lithium batteries play an extremely important role in human life. With the increase in the energy density of lithium batteries, many safety accidents caused by fires and explosions of lithium-ion liquid batteries have occurred around the world. At present, commercial batteries mostly use flammable organic electrolytes and lithium salts as electrolytes, which not only restricts the safe cycle of batteries, but also affects the development of a new generation of high-energy density batteries with metallic lithium as the negative electrode. Solid-state electrolytes have outstanding advantages in heat resistance, mechanical strength and electrochemical stability. They can be compatible with metallic lithium negative electrodes to prepare all-solid-state lithium metal high-energy batteries while ensuring safety.
[0003] However, most traditional polymer solid electrolytes have the disadvantages of poor electrical conductivity and mechanical strength, which limits the application of polymer solid electrolytes. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a solid electrolyte and a preparation method thereof, and a battery. The solid electrolyte provided in the present application has good electrical conductivity and mechanical strength.
[0005] In one aspect of the present invention, the present invention provides a solid electrolyte. According to an embodiment of the present invention, the solid electrolyte comprises a polymer and a lithium salt, and the polymer comprises:
[0006]
[0007] Among them, 5≤n≤30, 10≤m≤40.
[0008] According to the solid electrolyte of the above embodiment of the present invention, the polymer is a supramolecular structure, wherein there is a non-covalent bond (hydrogen bond, π-π stacking, etc.), these non-covalent bonds have supramolecular forces, have good self-assembly and self-recognition characteristics, and take hydrogen bonds as an example, multiple hydrogen bonds can be formed, which greatly enhances the mechanical strength and toughness of the polymer system. In addition, the existence of supramolecular forces can prompt the polymer to have good interface adaptability, ensuring stable fit with the electrode interface. In addition, the structure of the polymer contains a repeating unit composed of an ether oxygen bond, two six-membered rings and a benzene ring, and these repeating units form a folded structure, wherein the ether oxygen bond, as a connecting unit, can form hydrogen bonds, π-π stacking and other interactions with other functional groups, thereby driving the self-assembly of the polymer. And the benzene ring and the six-membered ring can provide a rigid skeleton, promote the stabilization of the assembly structure, and are conducive to improving the mechanical strength of the solid electrolyte. And the folded structure of the ether oxygen bond, the six-membered ring and the benzene ring can also effectively limit the crystallinity of the polymer to a certain range, thereby reducing the resistance inside the polymer electrolyte, making the transmission of lithium ions in the polymer smoother, and then can improve the conductivity of the solid electrolyte. Therefore, the solid electrolyte of the present application has good electrical conductivity and mechanical strength.
[0009] In addition, the solid electrolyte according to the above embodiment of the present invention may also have the following additional technical features:
[0010] In some embodiments of the present invention, the mass of the lithium salt accounts for 5% to 50% of the total mass of the solid electrolyte, thereby optimizing the formation of lithium ion channels and improving the transmission efficiency and conductivity of lithium ions.
[0011] In some embodiments of the present invention, the lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.
[0012] In some embodiments of the present invention, the solid electrolyte further includes an additive, thereby changing the chemical species on the electrode surface, thereby adjusting the interface affinity between the electrode and the solid electrolyte.
[0013] In some embodiments of the present invention, the mass proportion of the additive is 0.5% to 5% based on the total mass of the solid electrolyte, thereby enhancing the interfacial compatibility between the solid electrolyte and the electrode, reducing the interfacial resistance and the formation of lithium dendrites, and thus improving the cycle stability of the battery.
[0014] In some embodiments of the present invention, the additive includes fluoroethylene carbonate, thereby reducing the impedance of the battery, effectively inhibiting the decomposition of part of the solid electrolyte, and thus improving the stability of the battery.
[0015] In some embodiments of the present invention, the thickness of the solid electrolyte is 20 μm-200 μm, which is beneficial to improve the ionic conductivity of the solid electrolyte.
[0016] In the second aspect of the present invention, the present invention proposes a method for preparing the above-mentioned solid electrolyte. According to an embodiment of the present invention, the method comprises mixing polyethylene glycol, isophorone diisocyanate and a catalyst, heating for a first reaction to obtain a prepolymer; mixing the prepolymer, isophthalic acid hydrazide and a solvent for a second reaction to obtain a polymer solution; mixing the polymer solution with a lithium salt, removing the solvent, and hot pressing to obtain a solid electrolyte. Thus, a solid electrolyte with good conductivity and mechanical strength can be obtained.
[0017] In some embodiments of the present invention, the molar ratio of the polyethylene glycol to the isophorone diisocyanate is 1:(4-10). Thus, the number and ratio of the functional groups involved in the reaction can be controlled, the molecular chain can be smoothly extended, the structure of the polymer can be adjusted, and a suitable molecular structure can be obtained.
[0018] In some embodiments of the present invention, the molar ratio of the polyethylene glycol to the isophthalic acid hydrazide is 1:(2-5). Thus, the molecular weight of the polymer can be effectively controlled, which helps to prevent excessive cross-linking and branching, maintain the regularity of the molecular chain, and improve the mechanical properties of the polymer.
[0019] In some embodiments of the present invention, the molecular weight of the polyethylene glycol is 1000-20000. Thus, the molecular chain length and flexibility of the polymer can be effectively controlled, thereby facilitating the improvement of the mechanical strength of the solid electrolyte.
[0020] In some embodiments of the present invention, the catalyst includes dibutyltin dilaurate, thereby significantly increasing the speed of the polymerization reaction, thereby shortening the reaction time and improving production efficiency.
[0021] In some embodiments of the present invention, the solvent includes at least one of N,N-dimethylformamide, dimethyl sulfoxide, acetonitrile and tetrahydrofuran. Thus, a faster volatilization rate is beneficial to the rapid volatilization of the solvent and the formation of the solid electrolyte during the preparation process.
[0022] In some embodiments of the present invention, the temperature of the first reaction is 70° C.-90° C. Thus, the movement speed of the reaction molecules can be accelerated, the collision frequency between molecules is increased, and the polymerization reaction can be promoted.
[0023] In some embodiments of the present invention, the first reaction time is 1 hour to 5 hours. Thus, molecular segments with excellent supramolecular forces can be effectively obtained, which is beneficial to improving the mechanical strength of the solid electrolyte.
[0024] In some embodiments of the present invention, the temperature of the second reaction is 10° C.-30° C. This is beneficial to promote the reaction between isophthalic acid hydrazide and the terminal of the prepolymer and increase the rate of the second reaction.
[0025] In some embodiments of the present invention, the second reaction time is 20 hours to 30 hours. Thus, the terminal group structure and cross-linking degree of the polymer molecular chain can be adjusted, thereby improving the stability of the polymer.
[0026] In some embodiments of the present invention, step S3 includes: mixing the polymer solution, lithium salt and additives, removing the solvent, and hot pressing to obtain a solid electrolyte.
[0027] In some embodiments of the present invention, the temperature of the hot pressing is 50° C.-100° C. This can promote the bonding and physical entanglement between molecules and improve the compactness and mechanical strength of the solid electrolyte.
[0028] In some embodiments of the present invention, the hot pressing time is 20 min-60 min, which is conducive to forming a solid electrolyte membrane and obtaining a solid electrolyte with uniform thickness.
[0029] In a third aspect of the present invention, the present invention provides a battery. According to an embodiment of the present invention, the battery comprises the above-mentioned solid electrolyte or the solid electrolyte prepared by the above-mentioned method.
[0030] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0032] Figure 1 A flow chart of a method for preparing a solid electrolyte according to an embodiment of the present application is shown;
[0033] Figure 2 A picture showing the solid electrolyte of Example 1 subjected to a needle penetration test. DETAILED DESCRIPTION
[0034] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0035] In one aspect of the present invention, the present invention provides a solid electrolyte. According to an embodiment of the present invention, the solid electrolyte includes a polymer, and the polymer includes:
[0036]
[0037] Wherein, 5≤n≤30, 10≤m≤40. For example, n can be 5, 10, 15, 20, 25, 30, etc., and m can be 10, 20, 30, 40, etc.
[0038] According to the solid electrolyte of the above embodiment of the present invention, the polymer is a supramolecular structure, wherein there is a non-covalent bond (hydrogen bond, π-π stacking, etc.), these non-covalent bonds have supramolecular forces, have good self-assembly and self-recognition characteristics, and take hydrogen bonds as an example, multiple hydrogen bonds can be formed, and the mechanical strength and toughness of the polymer system can be improved. In addition, the existence of supramolecular forces can prompt the polymer to have good interface adaptability, ensuring stable fit with the electrode interface. In addition, the structure of the polymer also includes a repeating unit composed of an ether oxygen bond, two six-membered rings and a benzene ring, and these repeating units form a folded structure, wherein the ether oxygen bond, as a connecting unit, can form hydrogen bonds, π-π stacking and other interactions with other functional groups, thereby driving the self-assembly of the polymer. And the benzene ring and the six-membered ring can provide a rigid skeleton, promote the stabilization of the assembly structure, and are conducive to improving the mechanical strength of the solid electrolyte. And the folded structure of the ether oxygen bond, the six-membered ring and the benzene ring can also effectively limit the crystallinity of the polymer to a certain range, thereby reducing the resistance inside the polymer electrolyte, making the transmission of lithium ions in the polymer smoother, and then the conductivity of the solid electrolyte can be improved. Furthermore, by limiting the value range of n and m within the above range, the length of the molecular chain can be effectively controlled, the interaction between the chains and the steric hindrance can be reduced, which is beneficial to the migration of lithium ions and can improve the conductivity of the solid electrolyte. Therefore, the solid electrolyte of the present application has good conductivity and mechanical strength, which is beneficial to improving the cycle performance of the battery.
[0039] According to some embodiments of the present invention, the solid electrolyte further comprises a lithium salt. The addition of the lithium salt can, on the one hand, provide mobile lithium ions in the solid electrolyte, thereby increasing the concentration of lithium ions and thus improving the ionic conductivity of the solid electrolyte. On the other hand, it is conducive to forming a conductive polymer network to ensure the subsequent operation of the all-solid-state battery.
[0040] According to some embodiments of the present invention, based on the total mass of the solid electrolyte, the mass proportion of the lithium salt is 5% to 50%. For example, 5%, 10%, 20%, 40%, 50%. By limiting the mass proportion of the lithium salt to the above range, the distribution of lithium ions in the polymer can be controlled, the formation of lithium ion channels can be optimized, and the transmission efficiency and conductivity of lithium ions can be improved.
[0041] As an example, the lithium salt includes, but is not limited to, at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium hexafluorophosphate (LiPF6).
[0042] According to some embodiments of the present invention, the solid electrolyte further comprises an additive. The addition of the additive can interact with the electrode surface and change the composition of the solid electrolyte interface, thereby adjusting the interface affinity between the electrode and the solid electrolyte.
[0043] According to some embodiments of the present invention, based on the total mass of the solid electrolyte, the mass proportion of the additive is 0.5% to 5%. For example, 0.5%, 1%, 3%, 4%, 5%, etc. By limiting the mass proportion of the additive to the above range, the compatibility between the solid electrolyte and the electrode interface can be enhanced, the interface resistance and the formation of lithium dendrites can be reduced, and thus the cycle stability of the battery can be improved.
[0044] According to some embodiments of the present invention, the additive includes fluoroethylene carbonate. Fluoroethylene carbonate can form a tightly structured solid electrolyte interface on the electrode surface, which can reduce the impedance of the battery, effectively inhibit the decomposition of part of the solid electrolyte, and thus improve the stability of the battery.
[0045] According to some embodiments of the present invention, the thickness of the solid electrolyte is 20 μm-200 μm. For example, it can be 20 μm, 50 μm, 100 μm, 150 μm, 200 μm, etc. By limiting the thickness of the solid electrolyte to the above range, the transmission path of lithium ions can be shortened, the transmission efficiency of lithium ions can be improved, and the ionic conductivity of the solid electrolyte can be improved.
[0046] It should be noted that the thickness of the solid electrolyte refers to the size of the solid electrolyte material in a direction perpendicular to its plane.
[0047] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned solid electrolyte. According to an embodiment of the present invention, the method comprises:
[0048] S1: Polyethylene glycol, isophorone diisocyanate and a catalyst are mixed and heated to perform a first reaction to obtain a prepolymer.
[0049] In this step, under the action of a catalyst, polyethylene glycol and isophorone diisocyanate can undergo polymerization reaction to obtain a prepolymer, which is a supramolecular structure, wherein non-covalent bonds (hydrogen bonds, π-π stacking, etc.) are present, and these non-covalent bonds have supramolecular forces, have good self-assembly and self-recognition characteristics, and take hydrogen bonds as an example, can form the effect of multiple hydrogen bonds, greatly enhance the mechanical strength and toughness of the polymer system, and are conducive to improving the mechanical strength of the solid electrolyte. Wherein, the presence of supramolecular forces can prompt the polymer to have good interface adaptability, ensure stable fit with the electrode interface, make the transmission of lithium ions at the interface smoother, reduce transmission resistance, and improve the transmission efficiency of lithium ions.
[0050] According to some embodiments of the present invention, the molar ratio of the polyethylene glycol to the isophorone diisocyanate is 1:(4-10). For example, it can be 1:4, 1:10, 1:6, etc. By limiting the molar ratio of the polyethylene glycol to the isophorone diisocyanate within the above range, the number and proportion of the functional groups involved in the reaction can be controlled, the molecular chain can be smoothly extended, the structure of the polymer can be adjusted, and a suitable molecular structure can be obtained.
[0051] According to some embodiments of the present invention, the molecular weight of the polyethylene glycol is 1000-20000. For example, it can be 1000, 4000, 10000, 20000, etc. By limiting the molecular weight of the polyethylene glycol within the above range, on the one hand, it can promote the smooth polymerization reaction with isophorone diisocyanate. On the other hand, the molecular chain length and flexibility of the polymer can be effectively controlled, which is conducive to improving the mechanical strength of the solid electrolyte.
[0052] According to some embodiments of the present invention, the catalyst includes dibutyltin dilaurate. The selection of the above catalyst can significantly increase the speed of the polymerization reaction, thereby shortening the reaction time and improving production efficiency.
[0053] According to some embodiments of the present invention, the temperature of the first reaction is 70° C.-90° C. For example, it can be 70° C., 80° C., 90° C., etc. By limiting the temperature of the first reaction to the above range, the movement speed of the reaction molecules can be accelerated, the collision frequency between molecules is increased, and the polymerization reaction can be promoted.
[0054] According to some embodiments of the present invention, the time of the first reaction is 1h-5h. For example, it can be 1h, 2h, 3h, 4h, 5h, etc. By limiting the time of the first reaction to the above range, molecular segments with excellent supramolecular forces can be effectively obtained, which is beneficial to improving the mechanical strength of the solid electrolyte.
[0055] S2: The prepolymer, isophthalic acid hydrazide and solvent are mixed for a second reaction to obtain a polymer solution.
[0056] In this step, by mixing the prepolymer, isophthalic acid hydrazide and the solvent, the isophthalic acid hydrazide can chemically react and terminate the prepolymer in the solvent, which can control the length of the molecular chain and thus the molecular weight of the polymer, help prevent excessive cross-linking and branching, maintain the regularity of the molecular chain, and improve the mechanical properties of the polymer. On the other hand, the movement of the molecular chain can be inhibited, the activity of the molecular chain is reduced, and the molecular chains can be prevented from being entangled with each other.
[0057] According to some embodiments of the present invention, the molar ratio of the polyethylene glycol to the isophthalic acid hydrazide is 1:(2-5). For example, it can be 1:2, 1:3, 1:5, etc. By limiting the molar ratio of polyethylene glycol to isophthalic acid hydrazide within the above range, the molecular weight of the polymer can be effectively controlled, which helps to prevent excessive cross-linking and branching, maintain the regularity of the molecular chain, and improve the mechanical properties of the polymer.
[0058] According to some embodiments of the present invention, the solvent includes at least one of N,N-dimethylformamide, dimethyl sulfoxide, acetonitrile and tetrahydrofuran. By selecting the above solvent, the above solvent has a higher boiling point and a faster volatilization rate, which is conducive to the rapid volatilization of the solvent and the formation of the solid electrolyte during the preparation process.
[0059] According to some embodiments of the present invention, the temperature of the second reaction is 10° C.-30° C. For example, it can be 10° C., 20° C., 30° C., etc. By limiting the temperature of the second reaction to the above range, it is beneficial to promote the terminal reaction of isophthalic acid hydrazide with the prepolymer and increase the rate of the second reaction.
[0060] According to some embodiments of the present invention, the second reaction time is 20h-30h. For example, it can be 20h, 25h, 30h, etc. By limiting the time of the second reaction to the above range, the terminal group structure and cross-linking degree of the polymer molecular chain can be adjusted, thereby improving the stability of the polymer.
[0061] S3: The polymer solution is mixed with lithium salt, and after removing the solvent, hot pressing is performed to obtain a solid electrolyte.
[0062] In this step, a solid electrolyte can be obtained by mixing a polymer solution with a lithium salt, then naturally casting, drying at 60°C, and hot pressing after drying. Hot pressing can obtain a polymer electrolyte with a smoother surface and controllable thickness, which helps to enhance the interface contact between the polymer electrolyte and the electrode.
[0063] According to some embodiments of the present invention, the mixing in step S3 further includes an additive, and the method includes: mixing the polymer solution, the lithium salt and the additive, removing the solvent, and hot pressing to obtain a solid electrolyte. The addition of the additive can interact with the electrode surface, change the chemical species on the electrode surface, and thus adjust the interface affinity between the electrode and the solid electrolyte.
[0064] According to some embodiments of the present invention, the temperature of the hot pressing is 50°C-100°C. For example, it can be 50°C, 60°C, 80°C, 100°C, etc. By limiting the temperature of the hot pressing to the above range, on the one hand, it can promote the bonding and physical entanglement between molecules, and improve the compactness and mechanical strength of the solid electrolyte. On the other hand, it can promote the movement of polymer molecular segments and ensure the processability of the polymer system.
[0065] According to some embodiments of the present invention, the hot pressing time is 20 min-60 min. For example, it can be 20 min, 40 min, 60 min, etc. By limiting the hot pressing time within the above range, on the one hand, it can promote the close arrangement and interaction between polymer molecules, which is beneficial to improve the compactness and mechanical strength of the solid electrolyte. On the other hand, it is beneficial to form a solid electrolyte film and obtain a solid electrolyte with uniform thickness.
[0066] According to the preparation method of the solid electrolyte of the embodiment of the present invention, after polyethylene glycol and isophorone diisocyanate are polymerized under the catalysis of dibutyltin dilaurate, a polymer with non-covalent supramolecular forces can be obtained. The supramolecular non-covalent bond has good self-assembly and self-recognition characteristics. Taking hydrogen bonds as an example, multiple hydrogen bonds can be formed, which greatly enhances the mechanical strength and toughness of the polymer system. In addition, the existence of supramolecular forces can promote the solid electrolyte to have good interface adaptability and ensure stable fit with the electrode interface. Then, the molecular chain is chemically terminated in a solvent by isophthalic acid hydrazide, which can further control the length of the molecular chain. The molecular chain that is too long will show a large displacement resistance, which is not conducive to the migration of lithium ions between the molecular chains. The all-solid polymer electrolyte obtained by the above method has the characteristics of high mechanical strength and high conductivity, and can be used directly as an electrolyte, which solves the use of general organic electrolytes and the shortcomings of low strength and poor conductivity of traditional polymer electrolyte membranes. At the same time, the method of the present application reduces the operating cost and energy consumption, and ensures the output of the all-solid polymer electrolyte, which is conducive to industrial production.
[0067] In the third aspect of the present invention, the present invention provides a battery. According to an embodiment of the present invention, the battery includes the above-mentioned solid electrolyte or the solid electrolyte prepared by the above-mentioned method. As a result, the battery has good stability and safety performance. It should be noted that the features and advantages described above for the solid electrolyte and its preparation method are also applicable to the battery, and will not be repeated here.
[0068] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0069] Example 1
[0070] Preparation of solid electrolyte:
[0071] 1) polyethylene glycol, isophorone diisocyanate and dibutyltin dilaurate are mixed and reacted at 80° C. for 3 hours to obtain a prepolymer; wherein the molar ratio of polyethylene glycol to isophorone diisocyanate is 1:6;
[0072] 2) mixing the prepolymer, the catalyst isophthalic acid hydrazide and N,N-dimethylformamide, and reacting them at a temperature of 20° C. for 25 hours to obtain a polymer solution; wherein the molar ratio of polyethylene glycol to isophthalic acid hydrazide is 1:3;
[0073] 3) After mixing the polymer solution, the lithium salt lithium bis(trifluoromethanesulfonylimide) and the additive fluoroethylene carbonate, the mixture is naturally cast, and then dried at 60° C. After removing the solvent, the mixture is hot pressed at 100° C. to obtain a solid electrolyte with a thickness of 100 μm, wherein n of the polymer in the solid electrolyte is 20, m is 30, the mass proportion of the lithium salt is 30%, and the mass proportion of the additive is 1%.
[0074] Comparative Example 3
[0075] The solid electrolyte was prepared by replacing the polymer with polyethylene oxide, and the rest was the same as in Example 1.
[0076] The experimental parameters of Examples 1-17 and Comparative Examples 1-2 of the present application are shown in Table 1.
[0077] Table 1
[0078]
[0079] Testing and analysis
[0080] Under the same conditions, the solid electrolytes prepared in the above Examples 1-17 and Comparative Examples 1-3 were subjected to needle puncture tests and conductivity tests. The specific test methods are as follows:
[0081] Needle puncture test: The obtained polymer electrolyte membrane was placed on a pointed tweezer, and a downward external force was applied to observe whether the polymer electrolyte membrane was punctured by the pointed tweezer. Figure 2 The picture of the solid electrolyte of Example 1 undergoing a puncture test shows that the solid electrolyte membrane is not punctured under the action of external force, showing good mechanical strength.
[0082] Conductivity test: The obtained solid electrolyte membrane was cut into discs with a diameter of 12 mm. The positive electrode was lithium iron phosphate and the negative electrode was lithium metal. The button battery was assembled and its resistance was tested using an electrochemical workstation. The conductivity value was converted according to the resistance value.
[0083] Conductivity = resistance × cross-sectional area of solid electrolyte / length of solid electrolyte
[0084] The test results are shown in Table 2.
[0085] Table 2
[0086]
[0087]
[0088] Results and Discussion
[0089] As shown in Table 1-2, compared with Comparative Example 1, the solid electrolyte of Example 1-17 has good electrical conductivity and mechanical strength, and compared with Comparative Example 2, the solid electrolyte of Example 1-17 has good electrical conductivity. This is because the solid electrolyte of the present application contains repeating units composed of ether oxygen bonds, two six-membered rings and benzene rings, and these repeating units form a folded structure. Among them, the ether oxygen bond, as a connecting unit, can form hydrogen bonds, π-π stacking and other interactions with other functional groups, thereby driving the self-assembly of the polymer. The benzene ring and the six-membered ring can provide a rigid skeleton, promote the stabilization of the assembly structure, and help to improve the mechanical strength of the solid electrolyte. Moreover, the folded structure of the ether oxygen bond, the six-membered ring and the benzene ring can also effectively limit the crystallinity of the polymer, thereby reducing the resistance inside the polymer electrolyte, making the transmission of lithium ions in the polymer smoother, and then can improve the electrical conductivity of the solid electrolyte. Thus, the solid electrolyte of the present application has good electrical conductivity and mechanical strength.
[0090] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0091] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A solid electrolyte, characterized in that The solid electrolyte comprises a polymer and a lithium salt, wherein the polymer comprises: Among them, 5≤n≤30, 10≤m≤40.
2. The solid electrolyte according to claim 1, characterized in that Based on the total mass of the solid electrolyte, the mass proportion of the lithium salt is 5% to 50%; and / or, The lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.
3. The solid electrolyte according to claim 1 or 2, characterized in that The solid electrolyte further comprises an additive; and / or, Based on the total mass of the solid electrolyte, the mass proportion of the additive is 0.5% to 5%; and / or, The additive includes fluoroethylene carbonate.
4. The solid electrolyte according to claim 1 or 2, characterized in that The thickness of the solid electrolyte is 20 μm-200 μm.
5. A method for preparing the solid electrolyte according to any one of claims 1 to 4, characterized in that: include: S1, mixing polyethylene glycol, isophorone diisocyanate and a catalyst, heating and performing a first reaction to obtain a prepolymer; S2, mixing the prepolymer, isophthalic acid hydrazide and the solvent for a second reaction to obtain a polymer solution; S3. Mix the polymer solution with lithium salt, remove the solvent, and then perform hot pressing to obtain a solid electrolyte.
6. The method according to claim 5, characterized in that The molar ratio of the polyethylene glycol to the isophorone diisocyanate is 1:(4-10); and / or, The molar ratio of the polyethylene glycol to the isophthalic acid hydrazide is 1:(2-5); and / or, The molecular weight of the polyethylene glycol is 1000-20000; and / or, The catalyst comprises dibutyltin dilaurate; and / or, The solvent includes at least one of N,N-dimethylformamide, dimethyl sulfoxide, acetonitrile and tetrahydrofuran.
7. The method according to claim 5, characterized in that The temperature of the first reaction is 70°C-90°C; and / or, The first reaction time is 1h-5h.
8. The method according to claim 5, characterized in that The temperature of the second reaction is 10°C-30°C; and / or, The second reaction time is 20h-30h.
9. The method according to claim 5, characterized in that Step S3 comprises: mixing the polymer solution, the lithium salt and the additive, removing the solvent, and hot pressing to obtain a solid electrolyte; and / or, The temperature of the hot pressing is 50°C-100°C; and / or, The heat pressing time is 20min-60min.
10. A battery, characterized in that: The battery comprises the solid electrolyte according to any one of claims 1 to 3 or a solid electrolyte prepared by the method according to any one of claims 5 to 9.
Citation Information
Patent Citations
Method for synergistically toughening thermoplastic poly (urethane-urea) by using rigid and soft supramolecular fragments and application of thermoplastic poly (urethane-urea)
CN115716901A
Binder, manufacturing method thereof, electrode plate, lithium ion battery and wearable equipment
CN116463101A
Polymer solid electrolyte membrane and preparation method thereof
CN116598584A
In-situ polymerized solid-state battery with multilayer electrolyte and preparation method thereof
US20230216087A1
Aqueous polyurethane acrylate dispersions with a comb-like structure of the polymer
WO2012130762A1
Cited By
Solid polymer electrolyte, preparation method thereof, battery and electric device
CN121726521A